2015
DOI: 10.1104/pp.15.00991
|View full text |Cite
|
Sign up to set email alerts
|

EARLY SENESCENCE1 Encodes a SCAR-LIKE PROTEIN2 That Affects Water Loss in Rice

Abstract: . In plants, excessive water loss causes drought stress and induces early senescence. In this study, we isolated a rice (Oryza sativa) mutant, designated as early senescence1 (es1), which exhibits early leaf senescence. The es1-1 leaves undergo water loss at the seedling stage (as reflected by whitening of the leaf margin and wilting) and display early senescence at the three-leaf stage. We used map-based cloning to identify ES1, which encodes a SCAR-LIKE PROTEIN2, a component of the suppressor of cAMP recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 66 publications
0
46
0
Order By: Relevance
“…The pCA1301-C plasmid was transformed into Agrobacterium tumefaciens strain LBA4404 and the positive bacterial strains were introduced into the m34-z mutants using the A. tumefaciens -mediated transformation method (Rao et al, 2015). The primers used are listed in Supplementary Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The pCA1301-C plasmid was transformed into Agrobacterium tumefaciens strain LBA4404 and the positive bacterial strains were introduced into the m34-z mutants using the A. tumefaciens -mediated transformation method (Rao et al, 2015). The primers used are listed in Supplementary Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the rice tut1 mutant shows a pleiotropic phenotype during its entire life cycle, including shorter roots, reduced plant height, degenerating leaves, and degenerating panicles, suggesting that TUT1 functions as a housekeeping gene during rice growth and development. A recent study revealed that EARLY SENESCENCE1 (ES1), identical to TUT1, plays an important role in regulating water loss (Rao et al, 2015), suggesting that TUT1/ES1 is involved in various developmental and physiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…RLS1 encodes a previously uncharacterized nucleotide-binding site (NBS) containing protein with an armadillo (ARM) domain at its carboxyl terminus, and regulates rice leaf senescence through affecting chloroplast degradation (Jiao et al 2012). Rao et al found that the mutation of the gene encoding SCAR-like protein2 could cause drought stress and induce early senescence (Rao et al 2015). SCAR-like protein2 is a suppressor of cAMP receptor-like protein involved in actin polymerization and absolute ethanol.…”
Section: Pigment Content Measurementmentioning
confidence: 99%
“…The samples were then kept at 4 °C for 4 h. After fixation, they were rinsed with 0.1 M phosphate buffer (pH 7.0) and further fixed by 1 % osmium tetroxide for at least 1 h. The specimens were then dehydrated with a gradient of ethanol, embedded in small boxes and stained with lead citrate solution. The processed specimens were examined and photographed using a transmission electron microscope (Hitachi H-7650, Tokyo, Japan) (Gothandam et al 2005;Rao et al 2015).…”
Section: Transmission Electron Microscopy Analysis Of Chloroplast Ultmentioning
confidence: 99%
See 1 more Smart Citation